The teaching-learning process through the american culture with students of eighth year of basic education at “Ramón Paéz” educative unit in Latacunga during the academic cycle april 2014- august 2015 - Pichucho Pillo, Jenny Yolanda (2015)
This present investigate work was focused on improving the Teaching-Learning Process in the students from eighth year of basic education at “Ramón Paéz” Educative Unit in Latacunga city. The main objective of this investigation was to design workshops design with interesting activities based on American Culture in order to improve the students` English level. The main problem was that students were not learning a language through American Culture and it makes that they were not interested in learning English. In Fact, Students have lack of attention because they do not have the opportunity to acquire a foreign language through interesting activities which allow them have a better interest and knowledge in the English Learning. That is the reason why this investigation has as a purpose to design a workshop based on American Culture….